Perkembangan Sosial Ekonomi Papua Kabupaten Merauke 2005-2014 - Bedriati Ibrahim; Bunari; Sabaru, Nidandy (Jurnal Ilmu Sosial dan Humaniora, 2023)
The development of Merauke began with the first expansion in 2002 and then the last expansion in 2006. This expansion was carried out so that the government could manage its administrative area optimally and efficiently, besides that it was also intended as a way to initiate development in the region. The purpose of this research is to see how the relationship between the development of the region and the socio-economic conditions of the people in Merauke Regency. This research is a historical research in which the data to be used is historical or historical in nature. The results of this study conclude that regional expansion affects the socio-economic life of the people of Merauke Regency, both in the fields of education, health, employment and income.